IMPACT OF PERFORMANCE MANAGEMENT SYSTEM ON EMPLOYEE SATISFACTION (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
Employee engagement is closely connected to customer loyalty and overall profitability. When employees are positively engaged with their organization, they develop an emotional bond with the company, influencing their attitude towards customers. This leads to improved customer satisfaction and service quality. The retail industry should prioritize employee retention, customer satisfaction, and employee contentment to enhance efficiency. The study focus on employee satisfaction and its impact on organizational performance, with a specific case study conducted at Ezeelo Consumer Services Pvt. Ltd in Gurugram, which encompasses various studies on employee satisfaction, including factors influencing. Motivation theories are explored in the context of employee satisfaction. The study's primary objective is to assess the employee satisfaction level examining demographic characteristics, workplace and pay benefits, and factors affecting job satisfaction. The research methodology includes descriptive research, purposive sampling and data collection through surveys, observations, and interviews. Data analysis and interpretation reveal insights into employee satisfaction, gender differences, and age-related impacts. The study recommends various measures to improve employee satisfaction, such as regular team meetings, salary adjustments, and clearer communication of company policies. The conclusion underscores the significance of employee satisfaction in organizational success and highlights the need for motivational practices and improved communication within the organization.